The role of ultrasound examination in early detection of diseases: a case study - Olivia Ganna; Wenda Anastasia Indriyani (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Ultrasound examination (ultrasound) is one of the effective non-invasive diagnostic methods for early detection of various diseases. This study aims to explore the role of ultrasound in detecting diseases at an early stage through case studies of patients with various clinical complaints. By involving 60 participants, the majority of whom came from the local community, this program provides significant benefits for both the community and the participating students. The results showed that 96.6% of the participants had normal abdominal ultrasound results, although some abnormalities such as fatty liver, mild hepatomegaly, colessidiasis (gallstones), and kidney disorders were found. The obstetric examination showed normal pregnancy progression in two participants based on diagnostic parameters, which boosted their confidence while providing valuable hands-on learning opportunities for students. Overall, this program has succeeded in increasing public awareness of the importance of regular health checks while contributing to the development of student competencies. This success confirms the potential to expand similar initiatives to a wider region to improve overall public health outcomes.